Analysis of the factors of economic resilience to natural disasters: The case of Los Cabos, Mexico - Angélica Montano Armendáriz; Juan Carlos Pérez Concha (Atlantic Review of Economics (ARoEc), 2018)
The objectives of this document are two. Firstly, to identify the factors that foster resilience processes in tourist destinations which are vulnerable to natural hazards. The perceptual technical analysis allows us to make a diagnosis of the economic resilience capacity of the tourism sector in Los Cabos. The second objective assesses the economic-business dimension of tourism activity, based on the analysis of economic variables and tourism indicators that respond to the crisis caused by the hurricane. The empirical application was made, taking as a case study, the tourist destination of Los Cabos, Mexico. The multiple regression models of the variables are the basis for this quantitative research. These variables influence the processes of economic resilience in the sun and beach destinations. The results present an analysis of the resilience capacity of the destination regarding variables and factors such as employment, economic reactivation, urban equipment, infrastructure and tourist influx, financial income, investments, the behavior of companies and authorities in the face of natural disasters. The proposed Econometric Model was statistically significant, since the explained variance is 83%; therefore, the results refer that the tourist affluence and hotel infrastructure as well as the post-hurricane variable positively impacts the economic income in the tourist destination, through the multiplying effect of the investments that are generated to enhance the hydrometeorological phenomenon, which leads to greater dynamism in the local economy.
Keywords: Q26; R58; R11; 330; Tourism; Resilience; Los Cabos